Mapping Health Problems in Mulyodadi Hamlet, Bambanglipuro, Bantul: FGD Findings as a Basis for Health Promotion Training for Dukuh and Cadres - Nurhayyi, Asysyifa Ghofuri; Ramadona, Aditya Lia; Widia Adiratna; Renie Cuyno Mellen (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to asses the needs for identifying health challenges and the requirements for health promotion training in Mulyodadi Hamlet, Bantul. Method: The focus group discussion (FGD) method was employed in this study, involving dukuh and cadres, to obtain in depth information. Results: The FGD findings underscored the key health challenges in Mulyodadi, which include the prevalence of both communicable and non-communicable diseases, a lack of public awareness about the importance of a healthy lifestyle, and unequal access to health information within the community. It was also found that dukuh and cadres did not carry out widespread health promotion for the general public. Their educational efforts, often delivered through posyandu (integrated health service posts), were primarily targeted at parents of infants and toddlers, thus limiting their health promotion knowledge and skills to this context. Conclusion: To optimize their role in health promotion within the community, dukuh and cadres require health communication training, specifically elevator pitch skills training. This training will equip them with the ability to deliver concise, compelling, and effective health promotion messages, thereby addressing the identified health challenges more flexibly in terms of time and place.